Short report: no evidence of cardiotoxicity of atovaquone-proguanil alone or in combination with artesunate. - Gupta, R; Van Vugt, M; Paiphun, L; Slight, T; Looareesuwan, S; White, N; Nosten, F (2005)
Combinations are set to become the mainstay in treatment and prophylaxis of malaria due to Plasmodium falciparum. Various antimalarials have been implicated in cardiotoxicity via prolongation of the QTc interval. Atovaquone-proguanil is an effective and increasingly popular antimalarial choice when used alone or with artesunate in areas of drug resistance. We report the results of an investigation carried out on the Thai-Burmese border in 42 patients randomized to receive either atovaquone-proguanil or atovaquone-proguanil-artesunate for three days. Electrocardiographic recordings were made at baseline and one hour after each dose. There was no statistically significant change in QTc interval between baseline and any subsequent readings in either treatment group or the cohort as a whole. We conclude that atovaquone-proguanil shows no evidence of cardiotoxicity either alone or when combined with artesunate.